Measurement of the F-meson lifetime. - Jung, C; Abachi, S; Akerlof, C; Baringer, P; Beltrami, I; Blockus, D; Bonvicini, G; Brabson, B; Brom, J; Bylsma, BG; Chapman, J; Cork, B; et al. (1986)
The lifetime of the F meson has been measured to be (3.5-1.8+2.40.9) × 10-13 s by means of the F decay mode. The measurement was made with the High Resolution Spectrometer at the SLAC e+e- storage ring PEP at a center-of-mass energy of 29 GeV. © 1986 The American Physical Society.